Peptide Tethering: Pocket-Directed Fragment Screening for Peptidomimetic Inhibitor Discovery - Modell, Ashley E; Marrone, Frank; Panigrahi, Nihar R; Zhang, Yingkai; Arora, Paramjit S (Journal of the American Chemical Society, 2022)
Constrained peptides have proven to be a rich source of ligands for protein surfaces, but are often limited in their binding potency. Deployment of nonnatural side chains that access unoccupied crevices on the receptor surface offers a potential avenue to enhance binding affinity. We recently described a computational approach to create topographic maps of protein surfaces to guide the design of nonnatural side chains [J. Am. Chem. Soc. 2017, 139, 15560]. The computational method, AlphaSpace, was used to predict peptide ligands for the KIX domain of the p300/CBP coactivator. KIX has been the subject of numerous ligand discovery strategies, but potent inhibitors of its interaction with transcription factors remain difficult to access. Although the computational approach provided a significant enhancement in the binding affinity of the peptide, fine-tuning of nonnatural side chains required an experimental screening method. Here we implement a peptide-tethering strategy to screen fragments as nonnatural side chains on conformationally defined peptides. The combined computational–experimental approach offers a general framework for optimizing peptidomimetics as inhibitors of protein–protein interactions.